ADMISSIBILITY OF GENERIC MARKET MODELS OF FORWARD SWAP RATES. (2nd November 2012) - Li, Libo; Rutkowski, Marek
<x xml:space="preserve">Abstract</x> Our main goal is to re‐examine and extend certain results from the papers by Galluccio et al. and Pietersz and van Regenmortel. We establish several results providing alternate necessary and sufficient conditions for admissibility of a family of forward swaps, that is, the property that it is supported by a (positive) family of bonds associated with the underlying tenor structure. We also derive the generic expression for the joint dynamics of a family of forward swap rates under a single probability measure and we show that these dynamics are uniquely determined by a selection of volatility processes with respect to the set of driving martingales.